Involvement of heterologous ubiquitination including linear ubiquitination in Alzheimer’s disease and amyotrophic lateral sclerosis - Sato, Yusuke; Terawaki, Seigo; Oikawa, Daisuke; Shimizu, Kouhei; Okina, Yoshinori; Ito, Hidefumi; Tokunaga, Fuminori (Frontiers in Molecular Biosciences, 2023)
In neurodegenerative diseases such as Alzheimer’s disease (AD) and amyotrophic lateral sclerosis (ALS), the progressive accumulation of ubiquitin-positive cytoplasmic inclusions leads to proteinopathy and neurodegeneration. Along with the seven types of Lys-linked ubiquitin chains, the linear ubiquitin chain assembly complex (LUBAC)-mediated Met1-linked linear ubiquitin chain, which activates the canonical NF-κB pathway, is also involved in cytoplasmic inclusions of tau in AD and TAR DNA-binding protein 43 in ALS. Post-translational modifications, including heterologous ubiquitination, affect proteasomal and autophagic degradation, inflammatory responses, and neurodegeneration. Single nucleotide polymorphisms (SNPs) in SHARPIN and RBCK1 (which encodes HOIL-1L), components of LUBAC, were recently identified as genetic risk factors of AD. A structural biological simulation suggested that most of the SHARPIN SNPs that cause an amino acid replacement affect the structure and function of SHARPIN. Thus, the aberrant LUBAC activity is related to AD. Protein ubiquitination and ubiquitin-binding proteins, such as ubiquilin 2 and NEMO, facilitate liquid-liquid phase separation (LLPS), and linear ubiquitination seems to promote efficient LLPS. Therefore, the development of therapeutic approaches that target ubiquitination, such as proteolysis-targeting chimeras (PROTACs) and inhibitors of ubiquitin ligases, including LUBAC, is expected to be an additional effective strategy to treat neurodegenerative diseases.